Three-phase magnetic field tested in wireless power transfer system - Romba, Luis (2018)
This paper presents a magnetic field three dimensional mapping produced by a threephase prototype for wireless power transfer. The presented magnetic field mapping is a contribution to improve the design of electric vehicles battery chargers using the wireless power transfer. To collect the magnetic field data, a prototype was built, in order to support the tests. The prototype primary is an electrical three-phase system that allows to be connected electrically and geometrically in star or delta. The losses due to the magnetic field dispersion and the generated interferences in the surrounding equipment or in human body are discussed. The different standards organizations related to electric vehicles battery chargers are presented. Finally the magnetic field influence on the human body is addressed.